The Act Amending the Act on the Regulation of Electronic Commerce: New Rules for (New) Players in Electronic Commerce in Türkiye - Mesut Serdar Çekin (Annales de la Faculté de Droit d’Istanbul)
The rapid development in e-commerce has prompted a Turkish legislator to subject the existing law on its regulation to a comprehensive reform. In the process, the existing law was not substantially altered. Instead, the reform identified new players and imposed new obligations on them based on the net transaction volume. In particular, these players refer to large-scale online platforms on which e-commerce occurs. The express aim of the legislator is to prevent the formation of monopolies in this sector in general and to facilitate market access for small companies in particular. In this context, unfair business practices in B2B relationships have been defined. In addition, the new players, who were designated as e-business intermediary service providers and e-business service providers, must observe numerous restrictions with regard to business activities. In particular, this change is concerned with offers of goods, financial transactions, and delivery services on the online platforms. Another aspect of importance is the introduction of a licensing obligation for the exercise of e-commerce activities. To better monitor compliance with these obligations, the Turkish Ministry of Commerce has been empowered with certain responsibilities. The introduction of an Electronic Trade Information System also serves to improve monitoring. Finally, new sanction mechanisms have been introduced with the aim of effectively enforcing the obligations. The objective of this study is to present these new regulations.